Study of Ship Design Maninjau Lake Tourism by Using Catamaran Hull Type and Fiberglass Material - Trisyaldi, Ar; syahril, syahril; Purwantono, Purwantono; Waskito, Waskito; Primawati, Primawati (Teknomekanik, 2019)
Maninjau lake uses ships designed in a simple way without significant innovation from time to time. This case is caused by design methods that are based on hereditary knowledge from generations to generations, so that the ships that are made tend to have the same shape and size. Innovation is needed to get a higher level of efficiency and effectiveness on a ship. The innovation that needs to be done is the design of ships with a multi-hull shape or catamaran. The pre-design of the catamaran hull is based on using the comparation method as the dimension ratio of the ship, so that the dimensions of the ship are LWL = 4 m; LPP = 3.96 m; B = 1.7 m; B1 = 0.36 m; D = 0.7 m; d = 0.307 m. After that, testing the resistance (resistance) while determining the amount of Power needed. The next step is to analyze Stability and Seakeeping to determine the efficiency and effectiveness of the hull type. Analysis carried out on this type of hull was applied to several models, then the best hull design was found. Each design is distinguished by hull shape, but has the same displacement which is equal to 0.448 tons. The first model of the catamaran hull with the type of Flat Inside Symmetry; second with the type of symmetry Flat Outside; and the third type with gastric Asymmetry.